ANALYSIS OF BENJANG ART ON THE CULTURAL IDENTITY OF THE SUNDANESE COMMUNITY IN UJUNG BERUNG DISTRICT, EAST BANDUNG - Vilma Dewi Anggraeni (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
Benjang art is a traditional art form that reflects the cultural identity of the Sundanese community, particularly in the East Bandung region. The analyze of Benjang art represents the cultural values, traditions, and identity of the Sundanese people. A qualitative approach was employed with data collection techniques including observation, interviews, and documentation studies. The findings reveal that Benjang art serves not only as entertainment but also as a means of preserving cultural values and strengthening community identity. This study contributes theoretically to the relationship between art and cultural identity and offers practical benefits for the conservation of traditional arts.